Analysis of Energy Dissipation Characteristics of Damaged Sandstone under Impact Load - Feng Wang; Haibo Wang; Ying Xu; Bing Cheng; Qianqian Wang (Shock and Vibration)
Before rock burst, coal, and gas outburst dynamic load, rock mass in geotechnical engineering has been an indifferent degree of damage. The dissipation energy of rock mass under dynamic load reflects the difficulty of rock breaking. In view of the energy dissipation of damaged rock mass under dynamic load, the cyclic loading and unloading test is carried out to make sandstone in different damage states, and the damage degree of sandstone is characterized by the change of longitudinal wave velocity before and after cyclic loading and unloading. Then, the rock with different damage degrees is tested by adopting the split Hopkinson pressure bar (SHPB). Finally, the energy dissipation characteristics of damaged rock under impact load are analyzed. The results show that the damage factor of sandstone increases with the increase of the upper limit of stress after cyclic static loading. The dynamic strength and peak strain of damaged sandstone increase with the increase of impact pressure and decrease with the increase of damage degree. With the increase of damage degree of sandstone, the reflection energy and dissipation energy of sandstone increase, while the transmission energy decreases.